Azygos Lobe Detected by Thoracic Computed Tomography and Frequency of Concomitant Variations - Perincek, Gökhan; Avci, Sema; Çeltikçi, Pinar (Journal of Enam Medical College, 2019)
Background: The azygos lobe is a rare variation of the right upper lobe of the lung, and prevalence of it in the general population varies widely between 0.1% and 8%. It can be diagnosed easily by thoracic computed tomography. Objective: In this study, by thoracic computed tomography, azygos lobe frequency and associated variations were evaluated. Materials and Methods: In this study, 5854 thoracic computed tomography with and without contrast applied for patients in the Kars Harakani State Hospital Chest Diseases Polyclinic between January 2014 and January 2018 were screened retrospectively. Results: A total of 5854 thoracic computed tomography showed that frequency of azygos lobe was 1.09%. Out of 64 patients with azygos lobe, 36 (56.25%) were male and 28 (43.75%) were female. Bovine artery was found in 8 (12.5%) cases, right-left carotid artery common origin in 3 (4.68%) and aberrant right subclavian artery in 1 (1.56%). Conclusion: The detected azygos lobe frequency is similar to literature and the most common accompanying variation is bovine artery. J Enam Med Col 2019; 9(3): 177-180